2020
DOI: 10.1097/rhu.0000000000001581
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Refracture in Patients Older Than 65 Years With a Proximal Femur Fracture

Abstract: Objectives: To evaluate potential predictors of subsequent fracture and increased mortality in a population 65 years or older who suffered a proximal femur fragility fracture.Methods: This was a longitudinal study that included patients with a proximal femur fragility fracture, referred from the Orthopedics Inpatient Department to the Rheumatology Department's Fracture Liaison Service, from March 2015 to March 2017.Results: Five hundred twenty-two patients were included, with a median age (IQR) of 84 years (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 30 publications
6
19
1
1
Order By: Relevance
“…Another important finding of the study is that 60% of the subjects have high βCTX values and that βCTX values were significantly correlated with PTH values. Our data are in agreement with recent articles that have shown that the increase in serum βCTX values is related to bone fragility and can predict an increased risk of mortality [ 28 , 29 ]. The importance of the assessment of serum βCTX as a possible risk factor for hip fracture is supported by the fact that βCTX, similar to PTH, is significantly related to the CCI and the presence of previous fragility fractures [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Another important finding of the study is that 60% of the subjects have high βCTX values and that βCTX values were significantly correlated with PTH values. Our data are in agreement with recent articles that have shown that the increase in serum βCTX values is related to bone fragility and can predict an increased risk of mortality [ 28 , 29 ]. The importance of the assessment of serum βCTX as a possible risk factor for hip fracture is supported by the fact that βCTX, similar to PTH, is significantly related to the CCI and the presence of previous fragility fractures [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with recent articles that have shown that the increase in serum βCTX values is related to bone fragility and can predict an increased risk of mortality [ 28 , 29 ]. The importance of the assessment of serum βCTX as a possible risk factor for hip fracture is supported by the fact that βCTX, similar to PTH, is significantly related to the CCI and the presence of previous fragility fractures [ 25 , 29 ]. On this basis, βCTX could be considered as a possible indicator of reduced bone strength at the femoral level [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that the diagnosis of osteoporosis is associated with diverse complications after PFF. In this context, an increased fracture-associated mortality has been described [ 50 ], which was shown to be attenuated after the prescription of an anti-osteoporotic therapy [ 51 53 ]. Furthermore, a significantly enhanced risk for a secondary fracture after a previously undergone osteoporotic fracture as well as a reduction in both hip functional scores and QOL has been reported in cases of osteoporosis and the absence of adequate treatment [ 54 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Aside from the general reduction in cognitive capacities, mental disorders complicate the treatment of geriatric patients with PFF. Distinct neurologic diseases are known to increase the risk of refracturing after PFF [ 50 ]. In particular, dementia and delirium have been described to be associated with adverse outcomes in geriatric patients with PFF.…”
Section: Risk Factorsmentioning
confidence: 99%